Jakpreneur as an Entrepreneurial Support Ecosystem: A Review of the Literature - Situmeang, Fransiska Br.; Indriati , Fibria (Pelopor Publikasi Akademika, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in encouraging economic growth and job creation. However, MSMEs still face challenges related to entrepreneurial competence, access to financing, digital literacy, business legality, and market competition, as reflected by Indonesia's low entrepreneurship ratio at the global level. The government plays a crucial role as an enabler in overcoming this problem through the development of an entrepreneurial ecosystem. Jakpreneur, as an initiative of the Jakarta Provincial Government, is designed to strengthen the entrepreneurial ecosystem in Jakarta with a collaborative and integrated approach through seven integrated services (P1-P7). This article aims to analyze the role of Jakpreneur at the meso level in developing the entrepreneurial ecosystem in Jakarta using a qualitative literature study approach. The results show that Jakpreneur systematically supports each domain of the entrepreneurial ecosystem to act as an architect and facilitator of an adaptive and comprehensive ecosystem.